Pokok Pendidikan di Indonesia - Andre Fauzan; Vilsi Kholilah; Novia Dwi Ferlita (Jurnal Bintang Pendidikan Indonesia, 2025)
Education in Indonesia is one of the crucial sectors for national development. This article examines the key aspects of education in Indonesia, including the legal foundations, education policies, the education system, and the challenges faced in implementing education across the country. The discussion begins with an analysis of the National Education System Law (UUSPN) and how government policies, such as the 2013 curriculum, aim to improve the quality of education in Indonesia. This study also explores the important role of character education, the integration of technology in learning, and efforts to improve educational equity in remote areas. Based on a literature review and current statistical data, it is found that despite significant progress, Indonesia still faces major challenges, such as the quality disparity between urban and rural education, as well as limited access to higher education. Therefore, it is essential for the government and all stakeholders to continue efforts to enhance the quality and equity of education in Indonesia to achieve more inclusive and sustainable educational goals.